Mengukur Kinerja yang Ditinjau Dari Inovasi dan Governance - Diyan Lestari; Siti Nurjanah (Forum Kerjasama Pendidikan Tinggi, 2022)
The aims of this study is to analyze the impact of innovation strategy, corporate governance, and capital structure on firm performance. Innovation is very crucial for every companies, especially companies that engage in creative industry, such as consumer goods. Consumer goods companies should compete with their attractive packaging, products with high quality, and understand the market trend/ need. Creative promotion strategy must be implied in order to attract more consumers and win the competition. Innovation, should be the heart of a business and the rapid information technology development, companies may gain higher opportunities, but in the other hand it also gives many challenges since the competitors may become more innovative, and maybe they will gain more opportunities. So, every companies must develop creative strategy and become innovative. Corporate governance also plays such a big role to improve firm performance. This study aims to analyze the effect of innovation and corporate governance on firm performance. The sample data is consumer goods companies which are listed in IDX from 2012-2020 with purposive sampling as sampling technique. The result shows, innovation and board size do not affect the firm performance, while independent commissionaire, concentration ownership dan audit team affect firm performance